The Orbiting Carbon Observatory (OCO-2) tracks 2–3 peta-gram increase in carbon release to the atmosphere during the 2014–2016 El Niño. Issue 1 (December 2017) - Patra, Prabir; Crisp, David; Kaiser, Johannes; Wunch, Debra; Saeki, Tazu; Ichii, Kazuhito; Sekiya, Takashi; Wennberg, Paul; Feist, Dietrich; Pollard, David; Griffith, David; Velazco, Voltaire; et al.
Abstract The powerful El Niño event of 2015–2016 – the third most intense since the 1950s – has exerted a large impact on the Earth's natural climate system. The column-averaged CO2 dry-air mole fraction (XCO2 ) observations from satellites and ground-based networks are analyzed together within situ observations for the period of September 2014 to October 2016. From the differences between satellite (OCO-2) observations and simulations using an atmospheric chemistry-transport model, we estimate that, relative to the mean annual fluxes for 2014, the most recent El Niño has contributed to an excess CO2 emission from the Earth's surface (land + ocean) to the atmosphere in the range of 2.4 ± 0.2 PgC (1 Pg = 1015 g) over the period of July 2015 to June 2016. The excess CO2 flux is resulted primarily from reduction in vegetation uptake due to drought, and to a lesser degree from increased biomass burning. It is about the half of the CO2 flux anomaly (range: 4.4–6.7 PgC) estimated for the 1997/1998 El Niño. The annual total sink is estimated to be 3.9 ± 0.2 PgC for the assumed fossil fuel emission of 10.1 PgC. The major uncertainty in attribution arise from error in anthropogenic emission trends, satellite data and atmospheric transport.